Cuantificación de compuestos fenólicos y actividad antiinflamatoria de extractos de Senna occidentalis - Reategui Olortegui, Jaritza de Fatima (2025)
Objective: To quantify the phenolic compound content and evaluate the anti inflammatory activity of Senna occidentalis extracts. Methodology: The quantification of phenolic compounds was carried out using UV-Visible chromatographic techniques. Anti-inflammatory activity was assessed through the erythrocyte membrane stabilization assay, employing human red blood cells as the cellular model. Results: The leaf extracts of S. occidentalis exhibited the highest content of phenolic compounds, with 219.596 mg GAE/100 g of total phenols, 35.470 g quercetin/100 g of flavonoids, 20.647 mg cyanidin-3-glucoside/100 g of anthocyanins, and 0.077 mg/100 g of catechins, compared to the fruit and stem extracts. Regarding anti-inflammatory activity, all extracts showed IC₅₀ values > 1000 µg/mL, indicating an absence of anti-inflammatory effect at the tested concentrations. Conclusion: The leaves of S. occidentalis contain significantly higher levels of bioactive compounds compared to the fruit and stem. However, no anti-inflammatory activity was observed under the evaluated conditions and concentrations, suggesting the need for further studies including fractionation, structural characterization, and assessment in alternative biological models to better understand its therapeutic potential.